Habitual non-traumatic cricothyroid joint dislocation: a rare case of rotated larynx - Mohamad, Irfan; Al- Hadeethi, Yahia F. Hussein; Hassan, Nik Fariza Husna; Wan Din, Wan Shah Jihan; Abdullah, Baharudin (Malaysian Medical Association, 2012)
A case of a 21 year old gentleman is described, with no history of preceding trauma, presenting with intermittent dysphagia to solids and fluids for 4 years. Neck examination at rest was normal. However on deep inspiration, the right thyroid lamina protrudes or becomes more prominent. The patient is able to return the larynx to its normal position with manual manipulation. Laryngeal examination with fibreoptic scope during rest and deep breath shows gross rotation of the laryngeal structures for more than 60° on deep breath, with the vocal cords axis rotated to the left side. Management was conservative.